2012
DOI: 10.1111/j.1442-9071.2011.02678.x
|View full text |Cite
|
Sign up to set email alerts
|

Descemet's membrane substrate from human donor lens anterior capsule

Abstract: Human donor anterior lens capsule might therefore be a potential scaffold for the ex vivo expansion of human corneal endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
2
19
0
1
Order By: Relevance
“…Transplanting the LC with the epithelial side down resulted in a more rapid recovery and a transparent cornea at 6 months when compared with control eyes. LC has also been used successfully as a scaffold for the expansion of both limbal epithelial stem cells and HCEnC in vitro (Kopsachilis et al, ; Lachaud et al, ; Navaratnam et al, ; Yoeruek et al, ). These data suggested that LC could eventually be used for human transplantation, but prior to in vivo use, further characterization is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transplanting the LC with the epithelial side down resulted in a more rapid recovery and a transparent cornea at 6 months when compared with control eyes. LC has also been used successfully as a scaffold for the expansion of both limbal epithelial stem cells and HCEnC in vitro (Kopsachilis et al, ; Lachaud et al, ; Navaratnam et al, ; Yoeruek et al, ). These data suggested that LC could eventually be used for human transplantation, but prior to in vivo use, further characterization is required.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior capsular material could potentially be obtained as a by‐product of cataract surgery, one of the most frequently performed surgeries in the world. Preliminary studies have investigated the growth of corneal derived cells on the LC, namely, corneal epithelial and endothelial cells (Albert et al, ; Kopsachilis, Tsinopoulos, Tourtas, Kruse, & Luessen, ; Yoeruek et al, ). These studies however did not examine the additional physical properties of the LC that could make it suitable as a corneal endothelial scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the human lens capsule of donor globes was used as a scaffold for cultivation for human endothelial cells (Kopsachilis et al. ). In the present series, we therefore used the porcine lens capsule, which notably formed a roll when submerged in fluid (similarly to the stripped‐off human DM); in addition, it was resistant to tearing and easy to prepare.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous in vitro studies have reported the use of denuded DM and human anterior lens capsules (HALCs), as well as bioengineered matrices consisting of collagen or gelatin, or a combination of biopolymers, as potential carriers for cultured CECs. [9][10][11][12][13][14][15][16][17] These cell-carrier constructs should preferably be similar to an "original" DMEK-graft, since it has been reported for Descemet stripping (automated) endothelial keratoplasty (DSEK/DSAEK) that thicker grafts may interfere with visual outcome 18 and the biomechanical properties of cell-carrier constructs should allow implantation.…”
Section: Introductionmentioning
confidence: 99%